Agrobiodiversity Zones - Peru's flagship initiative at COP-16 - Ramirez, Marleni; Jones, Sarah; Estrada Carmona, Natalia; Quintana, Cristina; Fernandez, Elizabeth (2024)
At the COP16 on Biodiversity, last October in Cali, Colombia, Peru presented its in-situ/on farm agrobiodiversity conservation model during a prime-time side event titled “Agrobiodiversity Zones, Millenary agricultural conservation for Peru and world food security”, led by INIA, the Institute of Agrarian Innovation in the Ministry of Agriculture and Irrigation of Peru, MIDAGRI. This event presented the steps being taken by the government to officially recognize and support the silent effort of original people’s and rural communities in the conservation of the magnificent agrobiodiversity of Peru, fundamental for food security, climate change adaptation and sustainable development for the country and the world.